2021
DOI: 10.1039/d0na00697a
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of supramolecular anticancer drug amphiphiles with phospholipid membranes

Abstract: The shape of drug delivery vehicles impacts both the circulation time and the effectiveness of the vehicle. Peptide-based drug amphiphiles (DAs) are promising new candidates as drug delivery vehicles that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Tamoxifen [204], Cytarabine [205], 5-Fluorouracil [206,207], Daunorubicin [208,209], β-Lapachone [210], Minerval [211], Miltefosine [212], Tofacitinib [213], Edelfosine [214], Miltefosine [214], Perifosine [214], Camptothecin [215,216], Pirarubicin, Ellipticine [217], Perillyl alcohol [218], Cisplatin [219,220], Doxorubicin [179,217,221], 5-fluorouracil [206];…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
“…Tamoxifen [204], Cytarabine [205], 5-Fluorouracil [206,207], Daunorubicin [208,209], β-Lapachone [210], Minerval [211], Miltefosine [212], Tofacitinib [213], Edelfosine [214], Miltefosine [214], Perifosine [214], Camptothecin [215,216], Pirarubicin, Ellipticine [217], Perillyl alcohol [218], Cisplatin [219,220], Doxorubicin [179,217,221], 5-fluorouracil [206];…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
“…The initial stages of self-assembly are at microseconds to seconds time scales. For example, Tang and Manandhar et al used MD simulations to characterize the interactions of a similar DA system with a model membrane . More studies on these DAs using molecular dynamics (MD) simulations can be found elsewhere. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…For example, Tang and Manandhar et al used MD simulations to characterize the interactions of a similar DA system with a model membrane. 29 More studies on these DAs using molecular dynamics (MD) simulations can be found elsewhere. 6,15,16,28,30 ■ RESULTS AND DISCUSSION These TT1 molecules exhibit strong aromatic interactions that drive self-assembly.…”
Section: ■ Introductionmentioning
confidence: 99%